Variation in Quality of Primary-Care Services in Kenya, Malawi, Namibia, Rwanda, Senegal, Uganda and the United Republic of Tanzania - Kruk, Margaret E. (World Health Organization, 2021)
Although substantial progress has been made in reducing child and maternal deaths in the past 15 years, many women and children in low- and middle-income countries continue to die of avertable causes. To stimulate a concerted effort to narrow the gap between rich and poor countries, the United Nation’s sustainable development goals (SDGs) include new targets to reduce maternal mortality to less than 70 per 100 000 live births and to reduce deaths of children younger than five years to 25 per 1000 live births by 2030. In this paper, we analyse the variation in the quality of processes of care in health facilities in seven countries in subSaharan Africa for two primary-care services: (i) antenatal care and (ii) care of sick children, using observations of clinical care, a gold standard measure of process quality. The results will inform policy-makers about current performance and provide a starting point for a broader discussion of quality measurement in the SDG era.